Ethics, truth and social order - Grcic, Joseph (Sophia, 2006)
I criticize Rawls’ coherentist methodology and argue using the ideas of Talcott Parsons and Karl Popper that social and political structures flow from and are founded on human nature and arise from human beings seeking to satisfy their needs. For societies to exist and function in an efficient manner, certain ethical and political structures must obtain and that these structures would, in general, be required by the key elements of Rawls’ theory of justice and, as such would provide some of the necessary foundations for most components of his theory.